2013
DOI: 10.1007/s10517-013-2030-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dopamine on Ehrlich Ascites Carcinoma Cells

Abstract: Morphological studies showed that daily intraperitoneal injections of dopamine in doses of 10(-2)and 10(-1)M down-regulates the general number of cells in the Ehrlich ascites carcinoma in 10 and 30 times and decreases their diameter by 27% and 59%, respectively (as compared to the control animals received physiological saline). According to ultrastructural data these injections were followed by the abnormal changes in microvilluses, forming the specific moire fringes in cytosol, thickening of cortical layer, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Cancers can threaten both human physical and mental health, and many studies have paid more attention to the role of social psychological factors in the development and prognosis of cancers. 16,17 We explored whether CUMS could have an impact on the growth of subcutaneous xenografts of bladder cancer in nude mice in the current study. The results showed that the growth of transplanted tumors in the CUMS group was faster than that in control group.…”
Section: Discussionmentioning
confidence: 99%
“…Cancers can threaten both human physical and mental health, and many studies have paid more attention to the role of social psychological factors in the development and prognosis of cancers. 16,17 We explored whether CUMS could have an impact on the growth of subcutaneous xenografts of bladder cancer in nude mice in the current study. The results showed that the growth of transplanted tumors in the CUMS group was faster than that in control group.…”
Section: Discussionmentioning
confidence: 99%